Anarchism Potentialities towards Social Security in Indonesia - Dika Sri Pandanari; Setyo Widagdo; Harsuko Riniwati (Sekolah Pascasarjana Universitas Brawijaya, 2021)
Anarchism is the system of thought that arose in Indonesia nowadays. The research aims are to find clear views about anarchism by its literature, peoples, and observations of its movement in Indonesia. Then observe anarchism potentiality according to nationality by its movement which can affect alternative social movement in Indonesia. This research uses qualitative methods and applies comparison on literature as primary data and interviews as secondary data. The results of this research contain perspective anarchism views which are no longer stands against the states because of a new consciousness about real oppressor on all system especially the multinational institutions. Meanwhile, the potentiality of anarchism on small scales can be promoted as the alternative movement for the society to build better conditions for small scoops or locals of its base values which are to respect the nature of goodness and freedom on humanities.